Employment Chances Are “Satisfactory”: What Prevents Young People from Finding a Job in Conditions of Personnel Shortage? - O. B. Solodovnikova; E. E. Malkova; P. I. Tynkova (Социология власти)
The article analyzes the dysfunctional effects of the interaction between the education system and the labor market in modern Russia. It is shown that this problem is being actualized due to the shortage of personnel in particularly important sectors of the domestic economy, and that the existing system of training and retraining of personnel cannot cope with the elimination of the deficit. An administrative survey of Russian faculty conducted by IPEI RANEPA (N=21164) showed that a quarter of Russian faculty assess the employment chances of their graduates as “satisfactory” — and this despite the record shortage of personnel in the domestic labor market. The survey data, supplemented by the graduates’ own view of their employment (qualitative research, ten in-depth semi- structured interviews with students/graduates of Moscow universities), allowed us to draw conclusions about the primary factors preventing the effective use of youth personnel in the interests of the country’s economy. Among the macro-level factors are a lack of a well-thought- out system for converting university graduate competencies into qualifications required in the labor market (both in the humanities and natural sciences), as well as a lack of interregional forecasting of demand for certain specialties; as a result, labor force mobility is reduced. At the micro level, the lack of competencies for a competent job search among young people leads to the loss of valuable time for a career start and ineffective interactions with potential employers. A new national project “Personnel” has the potential to be an effective tool in addressing these challenges.